How is Film Philosophy Possible? - Milerius, Nerijus (Problemos, 2007)
The conditions of possibility of film philosophy are analyzed and discussed in the paper. It was not possible for film philosophy, as specific way of film interpretation, to appear because of the mutual hostility of philosophy to cinema and, vice versa, cinema to philosophy. It was searched for the preconditions of film philosophy not in works of philosophers but in three discourses on cinema. Film philosophy presents itself as the third discourse, following the first discourse, that of  inematographer, and the second discourse, that of film historian. The relations among those three cinematic discourses are examined. The conditions for transition from one discourse to the other are overviewed. It is concluded that the film philosophy discourse is not the propriety of academic philosophy alone. This kind of discourse could be represented by film makers and film historians who go beyond the limits of art discourse and seek to inscribe cinema into broader systems of understanding, philosophy here included.
Keywords: film philosophy, aesthetics, cinematic image